Historical Costs or Fair Value in Accounting: Impact on Selected Financial Ratios - Abdulsattar, Ahmed Raza Ayoob (2016)
In this thesis, we will be studying two asset measurement and valuation techniques non-current assets of companies, which are historical cost and fair value accounting. We study the implication of each technique and the resonating effect on the financial ratios, profitability and the gearing of companies. During last three decades there could be seen a visible trend of shifting from traditional historical costs accounting towards fair value accounting (or mark-to-market accounting respectively). The analytical part of this paper addresses the impact of studied valuation models on selected financial ratios with the purpose of identifying the most and the less sensitive ones on various valuation models. We also looked at the impact on the shareholder theory and the agency theory in conjunction with the models. For this study secondary data was collected from the 20 top performing companies in the fortune 500 companies in the US in 2015. The financial reports and ratios were analyzed for the study, to discuss the issues of currently used valuation models in financial reporting systems. In general, we find that adopting a fair value approach has limited effect on the financial ratios, profitability and borrowing ability of companies. Profitability in its nature is very subjective, especially to outward external factors.